Advanced Organic Chemistry: Part A Structure and Mechanism [5th ed.] - Carey, Francis A.; Sundberg, Richard J. (New York: Springer, 2007)
Since its original appearance in 1977, "Advanced Organic Chemistry" has found wide use as a text providing broad coverage of the structure, reactivity and synthesis of organic compounds. The Fourth Edition provides updated material but continues the essential elements of the previous edition. The material in Part A is organized on the basis of fundamental structural topics such as structure, stereochemistry, conformation and aromaticity and basic mechanistic types, including nucleophilic substitution, addition reactions, carbonyl chemistry, aromatic substitution and free radical reactions. The material in Part B is organized on the basis of reaction type with emphasis on reactions of importance in laboratory synthesis. As in the earlier editions, the text contains extensive references to both the primary and review literature and provides examples of data and reactions that illustrate and document the generalizations. While the text assumes completion of an introductory course in organic chemistry, it reviews the fundamental concepts for each topic that is discussed.The Fourth Edition updates certain topics that have advanced rapidly in the decade since the Third Edition was published, including computational chemistry, structural manifestations of aromaticity, enantioselective reactions and lanthanide catalysis. The two parts stand alone, although there is considerable cross-referencing. Part A emphasizes quantitative and qualitative description of structural effects on reactivity and mechanism. Part B emphasizes the most general and useful synthetic reactions. The focus is on the core of organic chemistry, but the information provided forms the foundation for future study and research in medicinal and pharmaceutical chemistry, biological chemistry and physical properties of organic compounds. The New Revised 5th Edition will be available shortly.
Keywords: Chemistry; Organic Chemistry